The effect of Ni and Si additions on the oxidation behaviour of Co-17Re-18Cr alloys. (October 2019) - Esleben, Katharina; Gorr, Bronislava; Christ, Hans-Jürgen; Mukherji, Debashis; Rösler, Joachim
Highlights: Increasing Ni additions improve the oxidation behaviour of Co-17Re-18Cr alloys due to enhanced Cr activity. Higher Ni contents accelerate the formation of the σ phase at elevated temperatures deteriorating the oxidation behaviour. A Si addition of 2 at.% shows a positive effect on the oxidation behaviour of the Co-17Re-18Cr-15Ni alloy at 900 °C–1100 °C. Si improves the oxidation resistance by enhancing the Cr activity but also influences the alloy microstructure. Abstract: The present study deals with the oxidation behaviour of three Co-17Re-18Cr-XNi (X = 8, 15, 25 at.%) alloys and one Co-17Re-18Cr-15Ni-2Si alloy in the temperature range 800 °C–1100 °C. The experimental results reveal improved oxidation resistance with increasing Ni concentration. It seems that Ni enhances the diffusion of Cr. However, higher Ni concentrations accelerate the formation of the Cr-rich σ phase detracting significant amounts of Cr from the matrix and deteriorating the corrosion resistance. Results of the oxidation tests reveal a positive effect of Si on the oxidation behaviour at 900 °C–1100 °C. It was found that Si enhances the Cr activity, though, facilitating the formation of the σ phase.